Inheritance of resistance in two Indian land races of Phaseolus vulgaris to Colletotrichum lindemuthianum - and DEEPIKA SUD, P.N. SHARMA, R.K. KAPILA, O.P. SHARMA (Indian Phytopathology, 2002)
Inheritance of resistance in two Indian land races, KRC 5 and KRC 8, of kidney bean (Phaseolus vulgaris) to race 903 (Beta) of Colletotrichum lindemuthianum was studied in pot and field tests. The segregation ratio of three resistant to one susceptible (3:1) and one resistant to three susceptible (1:3) in F2 generations revealed the presence of single dominant gene in KRC 5 and one recessive gene in KRC 8 for resistance, respectively, which was also confirmed by the segregation ratio of the backcross generation.